Silver Nanoparticles Based on Annona muricata Peel Reduce Cell Viability in Medulloblastoma and Neuroblastoma Cell Lines - Eduardo Lira-Díaz; Ricardo Cruz-Márquez; María Guadalupe González-Pedroza; Oscar Gonzalez-Perez; Raúl Alberto Morales-Luckie; Juan José Acevedo-Fernández (Journal of Nanotechnology)
Silver nanoparticles (AgNPs) can be obtained from plants and other organisms through green synthesis methods, considered eco-friendly and highly biocompatible. In this way, using plants with antitumor bioactive compounds increases cytotoxicity against tumor cells, acting in synergy between plant bioactive compounds (covering the nanoparticle) and AgNPs by itself. Acetogenins are the signature bioactive compounds present in Annona muricata (soursop) that induce tumor cell death by blocking respiratory complex 1 of the electron transport chain of the mitochondria, which is overexpressed in high-grade tumors such as medulloblastoma, a high-grade tumor of embryonic origin that affects the pediatric population. In this study, we evaluated the effects of AgNPs derived from an aqueous extract of soursop peel on neuroblastoma (CHP-212) and medulloblastoma (Daoy and D341 Med) cell lines. Additionally, we evaluated the viability of fibroblasts (HDFn) and macrophages (RAW 264.7) to observe biosafety in nontumor cells. Our results showed that AgNPs in soursop peel reduced the viability of CHP-212, Daoy, and D341 Med cell lines, in contrast to the fibroblast cell line. Thus, AgNPs derived from the aqueous extract of soursop peel may serve as a promising therapeutic tool for treating brain tumors.